Traditional Chinese medicine lowering lipid levels and cardiovascular events across baseline lipid levels among coronary heart disease: a meta-analysis of randomized controlled trials - Xie, Lihua; Liu, Jia; Wang, Xiaochi; Liu, Birong; Li, Jiaqi; Li, Jingen; Wu, Huanlin (Frontiers in Cardiovascular Medicine, 2024)
Background: Dyslipidemia is a critical driver for promoting the development of coronary heart disease (CHD), which further exacerbate risk of major adverse cardiovascular events (MACEs). Chinese herb medicine (CHM) plays an important role in regulation of lipid level and improvement of prognosis. However, few systematic reviews report whether the efficacy of CHM therapy for regulating lipid levels and lowering cardiovascular events is associated with baseline lipid levels. Methods: Randomized controlled trials (RCTs) assessing efficacy of CHM for lipid profiles and MACEs among CHD patients were searched in 6 databases. Two authors independently extracted studies according to a predesigned form. Cochrane risk of bias tool and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system were used to assess the methodological quality of included studies. The primary outcomes were blood lipid levels and MACEs including cardiovascular mortality, nonfatal myocardial infarction, revascularization, angina pectoris, heart failure and nonfatal stroke across baseline lipid levels. The secondary outcomes were individual component of the primary outcomes. Results: A total of 23 trials with 7,316 participants were included in this study. 377 cardiovascular events occurred in 3,670 patients in the CHM group, while 717 events in 3,646 patients in the western medicine alone group. Compared with western medicine alone, additional CHM significantly lowered low-density lipoprotein cholesterol (LDL-C) (MD=-0.46, 95%CI [-0.60, -0.32], P<0.00001, I 2 =96%). The risk reduction in MACEs associated with CHM vs western medicine therapy was 0.52 (95%CI [0.47, 0.58], P<0.00001, I 2 =0%), but varied by baseline LDL-C level (P=0.03 for interaction). Triglycerides (TG) level was also significantly lowered by additional CHM versus western medicine alone (MD=-0.27, 95%CI [-0.34, -0.20], P<0.00001, I 2 =81%), and risk reduction for MACEs also varied with baseline TG, with greater risk reduction in higher baseline TG subgroup (P=0.03 for interaction). Similar results were observed with total cholesterol (TC) and high-density lipoprotein cholesterol (HDL-C). Conclusion: Compared with western medicine alone, additional CHM was associated with lower risk of cardiovascular events and improvement of lipid profiles. Risk reduction for cardiovascular events was associated with baseline LDL-C and TG level.